2019
DOI: 10.3390/min9020074
|View full text |Cite
|
Sign up to set email alerts
|

Green Preparation of Nanoporous Pyrrhotite by Thermal Treatment of Pyrite as an Effective Hg(Ⅱ) Adsorbent: Performance and Mechanism

Abstract: The removal of Hg(II) from aqueous solutions by pyrrhotite derived from the thermal activation of natural pyrite was explored by batch experiments. The adsorption isotherms demonstrated that the sorption of Hg(II) by modified pyrite (MPy) can be fitted well by the Langmuir model. The removal capacity of Hg(II) on MPy derived from the Langmuir model was determined to 166.67 mg/g. The adsorption process of Hg(II) on MPy was well fitted by a pseudo-second-order model. The sorption of Hg(II) on MPy was a spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…Figure 3 show the SEM images of Py (A) and MPy (B). It can be observed that the natural pyrite crystal has a large size with smooth surfaces, while the modified pyrite has abundant inhomogeneous pores, resulting in modified pyrite with a higher porosity and higher specific surface area than natural pyrite, which confirms the result obtained from previous studies [31][32][33]. Based on previous studies by the authors, the sorption process of Hg(II) by MPy can be fitted by the Langmuir model and the Freundlich model.…”
Section: Structure and Property Of Modified Pyritesupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 3 show the SEM images of Py (A) and MPy (B). It can be observed that the natural pyrite crystal has a large size with smooth surfaces, while the modified pyrite has abundant inhomogeneous pores, resulting in modified pyrite with a higher porosity and higher specific surface area than natural pyrite, which confirms the result obtained from previous studies [31][32][33]. Based on previous studies by the authors, the sorption process of Hg(II) by MPy can be fitted by the Langmuir model and the Freundlich model.…”
Section: Structure and Property Of Modified Pyritesupporting
confidence: 85%
“…This result corresponds to the rising Based on previous studies by the authors, the sorption process of Hg(II) by MPy can be fitted by the Langmuir model and the Freundlich model. The Langmuir isotherm (R 2 = 0.9991) fit better than the Freundlich isotherm (R 2 = 0.9724) with regards to the sorption of Hg(II) onto MPy, and the maximum adsorption capacity of Hg(II) is 166.67 mg/g [31]. The specific surface area of MPy can be calculated from formula (2):…”
Section: Structure and Property Of Modified Pyritementioning
confidence: 96%
“…Pyrrhotite (MPy), derived from the thermal activation of natural pyrite, was used for the removal of Hg(II) from aqueous solutions [66]. The adsorption was related to the Langmuir model, with a maximum uptake of 0.83 mmol/g at pH 6, and fitted to the pseudo-second-order model.…”
Section: 6-diaminopyridine (Pd) and Polyamine Compoundsmentioning
confidence: 99%
“…There is also a noticeable trend of using natural materials in adsorption, including both waste rocks [21] as well as agricultural waste materials [22]. The clays as well as other materials are often modified thermally [23,24] or chemically [25][26][27] to enhance their adsorptive properties. As reported in [28], clay minerals are good adsorbents for metals, such as Cd(II), Cr(III), Cr(VI), Hg(II), Co(II), Cu(II), Zn(II), Pb(II), Ni(II), and Mn(II).…”
Section: Introductionmentioning
confidence: 99%